Teaching Innovation for the Challenges of the 21st Century: History of Art and Slow Movement - González Moreno, Fernando; García Alcázar, Silvia; Jaquero Esparcia, Alejandro; Morales Cano, Sonia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The confinement experienced during the Covid 19 pandemic forced us to face life at a slower rhythm. In this context, the Research Group of Interdisciplinary Studies of Literature and Art (LyA) (UCLM) proposed to develop a project to rethink our teaching methods under the perspective of the Slow Movement principles. The aim of this text is to show the experiences carried out in the Art History courses in the Degrees of Humanities and Social Studies (Faculty of Humanities of Albacete, UCLM) and History of Art (Faculty of Letters of Ciudad Real, UCLM).